2017
DOI: 10.1542/peds.2016-4023
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Binge Drinking Among US Adolescents, 1991 to 2015

Abstract: Recent declines in adolescent FBD have been driven by period and cohort effects. Attention is warranted for the slower declines in FBD seen among African American adolescents since 2007, a narrowing difference by sex, and a growing gap by SES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 47 publications
1
49
0
Order By: Relevance
“…The decline in underage drinking has occurred across a range of population subgroups, but not necessarily to the same extent. Quite a few countries have witnessed a gender convergence whereby the steeper downward trend in boys' alcohol use implies that they have approached the girls' lower prevalence of drinking [19,27,34,43,44,52,66,67,71,72]. Why the trends differ for boys and girls has not empirically scrutinised, which is another issue that future research should address.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decline in underage drinking has occurred across a range of population subgroups, but not necessarily to the same extent. Quite a few countries have witnessed a gender convergence whereby the steeper downward trend in boys' alcohol use implies that they have approached the girls' lower prevalence of drinking [19,27,34,43,44,52,66,67,71,72]. Why the trends differ for boys and girls has not empirically scrutinised, which is another issue that future research should address.…”
Section: Discussionmentioning
confidence: 99%
“…Moving to gender differences, two studies reported that girls had reduced their drinking to a greater extent than boys [35,37]. Several other found no gender differences [3,11,15,24,29,30,49,56,69], or that the reduction was greater, more consistent (across different drinking behaviours), or solely observed in boys [19,27,34,43,44,49,52,59,60,[65][66][67]71,72].…”
Section: Less Drinking Across Age and Gender?mentioning
confidence: 99%
“…APC effects models were estimated using the Clayton & Schifflers approach [32,33], as we have performed numerous times using MTF and other data sources [34][35][36][37][38]. Modeling strategies are complicated by the fact that APC are linearly dependent variables (cohort = period-age), thus their linear effects together are over-identified.…”
Section: Discussionmentioning
confidence: 99%
“…study is relevant to this question. Jang and colleagues examine frequent binge drinking among US adolescents participating in MTF and note a downward trend in cohort effects for adolescents born after 1986; that is, younger cohorts are less likely to binge drink . These cohort effects were remarkably similar in timing and magnitude to those for frequent cannabis use.…”
mentioning
confidence: 97%